Hubungan Komunikasi Orang Tua dengan Anak Terhadap Sikap Sosial Siswa - Muhamad Kepin Saputra; Muhammad Salam; Heri Usmanto (Journal of Civic Education, 2022)
This research aims to determine the effect of parent-child communication intensity on the social attitudes of eighth-grade students of SMP Negeri 10 Jambi City. The method used in this research is a quantitative approach using a survey. The data were analyzed using simple linear regression. Sources of data obtained from respondents are 66 students taken by random sampling technique. The occupations of parents of Grade VIII students at SMP Negeri 10 Jambi City are: entrepreneur, laborer, security guard, pedicab driver, civil servant, pedicab driver, and housewife. The conclusion of this research is: the intensity of parent-child communication has a significant effect on students' social attitudes in the form of honesty, discipline, courtesy, and tolerance. Low social attitudes can be overcome by establishing intensive communication between parents and children so that children can have an attitude that is in accordance with the norms and rules that apply in the family, school, and community environment.